The PGE(2) EP2 receptor accelerates disease progression and inflammation in a model of amyotrophic lateral sclerosis - Liang, Xibin (2008)
OBJECTIVE: Inflammation has emerged as an important factor in disease progression in human and transgenic models of amyotrophic lateral sclerosis (ALS). Recent studies demonstrate that the prostaglandin E(2) EP2 receptor is a major regulator of inflammatory oxidative injury in innate immunity. We tested whether EP2 signaling participated in disease pathogenesis in the G93A superoxide dismutase (SOD) model of familial ALS. METHODS: We examined the phenotype of G93A SOD mice lacking the EP2 receptor and performed immunocytochemistry, quantitative reverse transcriptase polymerase chain reaction, and Western analyses to determine the mechanism of EP2 toxicity in this model. RESULTS: EP2 receptor is significantly induced in G93A SOD mice in astrocytes and microglia in parallel with increases in expression of proinflammatory enzymes and lipid peroxidation. In human ALS, EP2 receptor immunoreactivity was upregulated in astrocytes in ventral spinal cord. In aging G93A SOD mice, genetic deletion of the prostaglandin E(2) EP2 receptor improved motor strength and extended survival. Deletion of the EP2 receptor in G93A SOD mice resulted in significant reductions in levels of proinflammatory effectors, including cyclooxygenase-1, cyclooxygenase-2, inducible nitric oxide synthase, and components of the NADPH oxidase complex. In alternate models of inflammation, including the lipopolysaccharide model of innate immunity and the APPSwe-PS1ΔE9 model of amyloidosis, deletion of EP2 also reduced expression of proinflammatory genes. INTERPRETATION: These data suggest that prostaglandin E(2) signaling via the EP2 receptor functions in the mutant SOD model and more broadly in inflammatory neurodegeneration to regulate expression of a cassette of proinflammatory genes. Inhibition of EP2 signaling may represent a novel strategy to downregulate the inflammatory response in neurodegenerative disease.